2011
DOI: 10.1007/s10570-011-9504-4
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical localization of a protein involved in synthesis of Gluconacetobacter hansenii cellulose

Abstract: Using subcellular fractionation and Western blot methods, we have shown that AcsD, one of the proteins encoded by the Acetobacter cellulose synthase (acs) operon, is localized in the periplasmic region of the cell. AcsD protein was heterologously expressed in Escherichia coli and purified using histidine tag affinity methods. The purified protein was used to obtain rabbit polyclonal antibodies. The purity of the subcellular fractions was assessed by marker enzyme assays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…One of the proteins coded by the operon, AcsD, has been reported to have a cylindershaped octamer structure localized in the periplasmic space, and it has been suggested that this structure may play a role in cellulose crystallization by functioning Patterns of cell movement include advancement in one direction rotation and then advancement in the other direction (b); oscillation side-to-side (c); spinning about axes (d); single directional non-linear advancement (e); and nonordered reversals (f) as a part of the cellulose synthesizing enzyme complex (Saxena et al 1994;Hu et al 2010;Iyer et al 2011). The purpose of this study was to characterize the disruption mutant to aid in determining the function of AcsD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the proteins coded by the operon, AcsD, has been reported to have a cylindershaped octamer structure localized in the periplasmic space, and it has been suggested that this structure may play a role in cellulose crystallization by functioning Patterns of cell movement include advancement in one direction rotation and then advancement in the other direction (b); oscillation side-to-side (c); spinning about axes (d); single directional non-linear advancement (e); and nonordered reversals (f) as a part of the cellulose synthesizing enzyme complex (Saxena et al 1994;Hu et al 2010;Iyer et al 2011). The purpose of this study was to characterize the disruption mutant to aid in determining the function of AcsD.…”
Section: Discussionmentioning
confidence: 99%
“…In G. xylinus, normal arrangement of the linear terminal complexes appears as a single row along the longitudinal axis of the cell (Kimura et al 2001). The AcsD octamer was determined to be localized in the same linear arrangement within the cell's periplasm (Hu et al 2010;Iyer et al 2011;Sunagawa et al 2013). The linear TC orientation on the mutant cells did not have this same linear arrangement; instead, the linear TCs appeared abnormal as they were often observed to be positioned on the transverse, diagonal, or longitudinal axis (Figs.…”
Section: Acsd Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The other protein we examined for impact on cellulose synthesis activity was AcsD, which is a periplasmic localized protein [32].…”
Section: The Catalytic Core Of the Cscmentioning
confidence: 99%
“…AcsD is the only Acs protein of Gluconacetobacter whose crystal structure has been determined (11); it is an octameric protein assembly localized to the periplasmic space (11,12). It may function as a cellulose chaperone, directing the newly synthesized cellulose chains to AcsC in the outer membrane to prevent accumulation of rogue strands in the periplasm.…”
mentioning
confidence: 99%